Fundamental Recommendations for the Design Configuration of Rotor Shafts for Use in Electric Motors and Generators. (2016) - Ahmad, Hayder Y.; Bonnieman, David
Abstract: This paper presents a real case study of a generator that successfully passed testing in one environment; although, the rotor shaft failed mechanically when the testing environment had been customized. So, to design a robust rotor shaft, major factors that affect the life time of the rotor shaft should be addressed and considered. These major factors which are addressed in this paper are fundamental geometry driven stress concentration factors, fretting driven fatigue stress concentration effects and vibration natural frequency. Finite elements analysis and extensive mechanical vibration tests were used to achieve a robust shaft design.